ATP8a1, an IFT27 binding partner, is dispensable for spermatogenesis and male fertility. Issue 5 (6th April 2021) - Yap, Yi T.; Li, Yu H.; Li, Wei; Banerjee, Probal; Zhang, Zhibing
Abstract: Intraflagellar transport 27 (IFT27) is a key regulator for spermiogenesis and male fertility in mice. ATP8a1, a protein involved in the translocation of phosphatidylserine and phosphatidylethanolamine across lipid bilayers, is the strongest binding partner of IFT27. To investigate the role of ATP8a1 in spermatogenesis and male fertility, the global Atp8a1 knockout mice were analyzed. All mutant mice were fertile, and sperm count and motility were comparable to the control mice. Examination of testis and epididymis by hematoxylin and eosin staining did not reveal major histologic defects. These observations demonstrate that ATP8a1 is not a major spermatogenesis regulator. Given that a tissue‐specific paralogue of ATP8a1, ATP8a2, is present, further studies with double‐knockout models are warranted to delineate any compensatory functions of the two proteins.